Innovative Connotations in The Noble Quran - Mahmudi, Ihwan; Reformawati, Nur (Jurnal Diskursus Islam, 2023)
The one who looks at the Qur’an will find that the saying has been attributed to a number of sources, some of which have nothing to do with the creation of man, and others are like the earth in the Almighty’s saying: (Then He turned to the sky when it was smoke, and He said to it, and to the earth are our creatures) In this preamble, I will address its content with human creation by mentioning it only, not by explaining its connotations and meanings, but rather narrating them in a narration, for the reason that the Qur’an ascribed the saying to his property that is related to human creation other than mouths and tongues. About the other in saying that they complement each other and look To the Qur`an we find from sources say: 1. Self: The Almighty said: (N) says the same is lost on what is fraited in the side of God. 2. - Leather: The Almighty said: (They said to their skin, you have not seen our priority Everything is your first time and to return. 3. Hands and legs: The Almighty said: (and spoke our hands and see their legs.) 4. This is in addition to the mouths of the topic of the search. 1. Surah Fussilat verse 11. 2. Surah Al-Zumar verse 56. 3. Surah Fussilat verse 21. 4. Surah Yasin, verse 65.